An approach to neonatal lamb post-mortem examinations. (2nd July 2019) - Gascoigne, Emily; Davies, Peers
Abstract : Neonatal lamb mortality is a significant threat to welfare and production in commercial sheep flocks and is defined as the death of lambs during the first week of life with the predominant risk period being the first 48 hours. Lamb mortality between scanning and sale ranges from 10 to 25%, with examples of losses between 0 to 48 hours old ranging from 5.9% to 12.5%. Lamb post-mortem examinations are a tool which can facilitate achieving further understanding of the scale and cause of losses for flocks. We discuss an approach to postmortem examinations on neonatal lambs, the common differentials affecting lambs between 0 and 48 hours old, and discuss the role of farmers in surveillance.